Clinical significance of autoantibody positivity in idiopathic pulmonary fibrosis. (August 2019) - Ghang, Byeongzu; Lee, Jungsun; Chan Kwon, Oh; Ahn, Soo Min; Oh, Ji Seon; Hong, Seokchan; Kim, Yong-Gil; Yoo, Bin; Jeong, Woo Seong; Kim, Jinseok; Lee, Chang-Keun
Abstract: Rationale: The concept of interstitial pneumonia with autoimmune features (IPAF) was recently proposed by the American Thoracic Society. However, the clinical significance of the serologic domain of IPAF has not yet been established in idiopathic pulmonary fibrosis (IPF). Objectives: We aimed to investigate the clinical significance of autoantibody positivity in IPF. Methods: We retrospectively reviewed the records of 512 patients diagnosed as IPF from January 2007 through March 2014. The patients were divided into two subgroups: (i) an autoantibody-positive IPF subgroup (n = 138), consisting of patients with anti-neutrophil cytoplasmic antibody (ANCA) or autoantibodies that met the criteria for the IPAF serologic domain; (ii) a lone IPF subgroup (n = 374), consisting of the rest of the IPF patients. Measurements and main results: Autoantibody-positivity (HR 0.736, p = 0.043) was an independent risk factors for 5-year mortality on multivariable analysis in the overall IPF patients. In the autoantibody-positive IPF patients, use of glucocorticoid (not for management of acute exacerbation, HR 2.121, p = 0.019), use of immunomodulators (HR 0.310, p = 0.002), malignancy (HR 3.359, p = 0.002), baseline forced vital capacity (HR 0.974, p = 0.017), baseline diffusing capacity of the lung for carbon monoxide (HR 0.981, p = 0.041), and baseline 6-min walk test distance (HR 0.996, p = 0.002) were independent risk factors for 5-year mortality. Conclusions: Presence of ANCA or autoantibodies of the IPAF serologic domain in IPF patients is associated with better survival outcomes, and the use of immunomodulators is associated with superior survival outcomes. Highlights: Autoantibody-positive IPF patients are not classified as having IPAF or CTD-UIP. The guidelines for treating these patients do not recommend the use of immunosuppressive agents. Autoantibody positivity, defined by the IPAF serologic domain and ANCA, is associated with a good prognosis in IPF patients. The use of immunosuppressive agents was associated with a good prognosis in autoantibody-positive IPF patients but not in the rest of the IPF patients. Autoantibody-positive IPF may have an origin that is similar to that of CTD-UIP, and one that is different from the rest of the IPF.